Sexual health information seeking: a survey of adolescent practices. Issue 23 (4th March 2013) - Whitfield, Clare; Jomeen, Julie; Hayter, Mark; Gardiner, Eric
Abstract : Aims and objectives: To identify sources of information and support preferred by young people to understand adolescent practices as adolescents develop a sexual health knowledge base. Background: Statistics suggest that adolescents are not always making safe sexual health decisions. It is essential to develop an understanding of preferred sources of information and support to structure health and education services so that adolescents develop skills and knowledge to make safer choices. Design: A cross‐sectional survey design. Methods: A wide‐ranging questionnaire was developed using validated questions, drawn from similar adolescent lifestyle surveys and adapted with guidance from an advisory group; 2036 13–16‐year‐olds responded. Two questions, reporting information sources adolescents find useful and sources of approachable support, are considered here. Results: Adolescents find informal sources more useful and experience higher levels of comfort accessing informal support especially from their best friends and mothers. Of formal provision, school‐based sources are preferred; however, sexual health information seeking is gendered and changes across year groups. The range of sexual health information sources adolescents access increases with age, and how they access these information sources changes as sexual activity increases and the information becomes more relevant. Conclusions: The findings support the targeting of sexual health provision in relation to age and gender and suggest a youth‐focused approach to formal provision, including outreach working and a collaborative relationship with adolescents and parents. Relevance to clinical practice: The findings contribute to an understanding of sources of information and support preferred by adolescents. In particular, they need to reconsider how services external to the school may be developed so they are youth‐focused and approachable. Nurses need to consider how best to work in partnership with adolescents and their families to disseminate accurate information and develop relevant services.